SPE Annual Technical Conference and Exhibition 2001
DOI: 10.2118/71337-ms
|View full text |Cite
|
Sign up to set email alerts
|

Compaction-induced porosity/permeability reduction in sandstone reservoirs: Data and model for elasticity-dominated deformation

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractOpen-literature and new experimental compaction data of five reservoir and 16 outcrop sandstones are used to delineate the near-elastic, inelastic and failure domain in 3D-stress space for porosity classes 5 to 15%, 15 to 25% and 25 to 35%. Applications of this compaction-domain model include the analysis of the extent of the near-elastic domain (where elasticity theory can be used to describe and predict rock deformation), the pore volume compressibility (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For the reservoir rock, for which we set an initial porosity φ 0 = 16%, laboratory experiments have shown that permeability changes significantly less than 1 order of magnitude [ Schutjens et al ., ]. We apply a permeability law that is based on the modified Kozeny‐Carman relationship, which is commonly used to model permeability changes in reservoir rocks [ Zoback , , and references therein]: κ=κ0φφcφ0φc31+φcφ01+φcφ2 where φ c is the percolation porosity, which is the limiting porosity at which the pores are disconnected and no longer contribute to flow.…”
Section: Model Setupmentioning
confidence: 99%
“…For the reservoir rock, for which we set an initial porosity φ 0 = 16%, laboratory experiments have shown that permeability changes significantly less than 1 order of magnitude [ Schutjens et al ., ]. We apply a permeability law that is based on the modified Kozeny‐Carman relationship, which is commonly used to model permeability changes in reservoir rocks [ Zoback , , and references therein]: κ=κ0φφcφ0φc31+φcφ01+φcφ2 where φ c is the percolation porosity, which is the limiting porosity at which the pores are disconnected and no longer contribute to flow.…”
Section: Model Setupmentioning
confidence: 99%
“…For this study, a failure criterion with a cap to represent pore collapse was used. This cap model was originally developed by NGI for application to sandstone reservoirs by Schutjens et al (2004) and later applied to carbonate reservoirs.…”
Section: Spe-171993-msmentioning
confidence: 99%
“…The precipitation of these salts can lead to disastrous damage in building and statues made with porous materials. ,,,,,, This damage can be made worse by treatments that aim to waterproof the building materials as this can encourage subflorescence that weakens the outer layer . Pore network models have also been used to study and predict drying of pure liquid porous media without salt precipitation , and to study combined evaporation and salt precipitation in porous media. ,, Also, for CO 2 sequestration processes, precipitation of salts, mainly consisting of halite (NaCl), can be a serious source of problems during CO 2 injection because this can lead to reductions in porosity and permeability of the reservoir in the vicinity of the wellbore. ,, Oil reservoirs have a wide range of wetting states, and given the strong influence of capillary forces outlined above, this may have a significant impact on halite deposition. The effect of these different porous media wetting states on the different stages of evaporation and the subsequently deposited salt is not well understood and remains one of the open problems in the field, especially during the storage of supercritical CO 2 in depleted oil and gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%